States of denial : knowing about atrocities and suffering / Stanley Cohen. - Cohen, Stanley, 1942- (Polity, 2001)
This text offers a comprehensive study of both the personal and political ways in which uncomfortable realities are avoided and evaded. It ranges from clinical states of depression, to media images of suffering.